(untitled) (Palestine Issues on Indonesian Society, 2024)
This paper investigates the role of Indonesia’s Muslim majority in mobilizing support for Palestine, focusing on the intersection of religion, politics, and activism. Indonesia, as the world’s largest Muslim-majority country, has long demonstrated strong solidarity with Palestine, both in terms of public opinion and political advocacy. This study examines the factors that contribute to this mobilization, including religious teachings, political ideologies, and the influence of Islamic organizations in shaping the discourse on Palestinian rights. Drawing on interviews with religious leaders, political activists, and members of Islamic organizations, this paper explores how Islamic narratives of justice, resistance, and anti-colonial struggle resonate with Indonesia’s Muslim population. The research also addresses how religious identity shapes not only public sentiment but also formal political actions, such as Indonesia’s participation in international forums advocating for Palestinian statehood. The study argues that the Palestinian cause occupies a central place in Indonesian Islamic discourse, and explores how this has influenced Indonesia’s broader foreign policy and its role in global humanitarian advocacy.